Growth inhibitory response and ultrastructural modification of oral-associated candidal reference strains (ATCC) by Piper betle L. extract - Nordin, M.A.F.; Himratul-Aznita, Wan Harun; Razak, Fathilah Abdul; Musa, M.Y. (Nature Publishing Group, 2014)
Candida species have been associated with the emergence of strains resistant to selected antifungal agents. Plant products have been used traditionally as alternative medicine to ease mucosal fungal infections. This study aimed to investigate the effects of Piper betle extract on the growth profile and the ultrastructure of commonly isolated oral candidal cells. The major component of P. betle was identified using liquid chromatography-mass spectrophotometry (LC-MS/MS). Seven ATCC control strains of Candida species were cultured in yeast peptone dextrose broth under four different growth environments: (i) in the absence of P. betle extract; and in the presence of P. betle extract at respective concentrations of (ii) 1 mg⋅mL−1; (iii) 3 mg⋅mL−1; and (iv) 6 mg⋅mL−1. The growth inhibitory responses of the candidal cells were determined based on changes in the specific growth rates (µ). Scanning electron microscopy (SEM) was used to observe any ultrastructural alterations in the candida colonies. LC-MS/MS was performed to validate the presence of bioactive compounds in the extract. Following treatment, it was observed that the µ-values of the treated cells were significantly different than those of the untreated cells (P<0.05), indicating the fungistatic properties of the P. betle extract. The candidal population was also reduced from an average of 13.44×106 to 1.78×106 viable cell counts (CFU)⋅mL−1. SEM examination exhibited physical damage and considerable morphological alterations of the treated cells. The compound profile from LC-MS/MS indicated the presence of hydroxybenzoic acid, chavibetol and hydroxychavicol in P. betle extract. The effects of P. betle on candida cells could potentiate its antifungal activity.